A new restricted-range Melanorivulus (Cyprinodontiformes: Rivulidae) from the upper rio Guaporé, Chapada dos Parecis, Brazil - Nielsen, Dalton Tavares Bressane; Ohara, Willian Massaharu (Zootaxa, 2024)
A new species of Melanorivulus, belonging to the Melanorivulus zygonectes species group, is described from the rio Galera, a tributary of the right bank of the upper rio Guaporé, Amazon basin, Mato Grosso state, Brazil. It is diagnosed from congeners by the following combination of characters: absence of pelvic fins; presence of a black band along the entire caudal-fin margin in males, typically more conspicuous on dorsal and ventral portions; presence of a wide oblique bars anteriorly and wide chevron-like marks posteriorly to middle of flank. This is the first record of the genus Melanorivulus for the rio Madeira basin.